Branding Bhakti: Krishna Consciousness and the Makeover of a Movement - Karapanagiotis, Nicole (Framing the Global Ser., 2021)
Branding Bhakti not only investigates the methods the ISKCON movement uses to position itself for growth but highlights devotees' painful and complicated struggles as they work to transform their shrinking, sectarian movement into one with global religious appeal.